Research and Simulation of Control Strategy of the Regenerative Braking Energy Recycle of Hybrid Vehicle - Gao Lijie (Jixie chuandong)
Aiming at the characteristic of hybrid vehicle powertrain system,a new control strategy of regenerative braking is put forward based on the classification of braking intensity,in developing the simulation model,many vital factors,such as the initial temperature of battery system,the transfer efficiency of motor and the driving torque of engine are taken into consideration,and the experimental data of this specific car are put into MATLAB.The simulation result shows that what proposed control strategy can achieve high performance of energy recycle with the limitation of ECE rules,when a soft or moderate braking intensity is needed.